Eastern Art Online : Yousef Jameel Centre for Islamic and Asian Art - Ashmolean Museum (2010)
[Engl.:] The Eastern Art collections at the Ashmolean comprise around 30,000 objects including ceramics, textiles, sculpture, metalwork, paintings, prints, and other decorative arts